PERCEPTION OF TABOO HUMOR IN INTERCULTURAL ONLINE COMMUNICATION THROUGH SOCIAL MEDAI - Siboro, Meliana; Mono, Umar; Perangin-angin, Alemina Br. (Universitas Muhammadiyah Tapanuli Selatan, 2022)
As the pandemic is forcing people to stay at home for a longer period of time, activities and social interactions also moved from physical to digital world. This shift of change revealed the unfavorable nature of Indonesians’ netizen behaviors in the internet, labelled as ‘The rudest netizen’ in Southeast Asia for their ferociousness in online communication. This paper aims to investigate the perception of Indonesian internet users at the use of taboo words used in humor in intercultural online communication. Primary and secondary data were collected by observational method and qualitative descriptive method was used to present the analysis. The finding of this paper suggested that generally, 75% of the audiences on TikTok and YouTube have positive perception toward the usage of taboo words in public setting by taking context awareness, timing and intent into consideration.